2008
DOI: 10.2478/v10044-008-0006-4
|View full text |Cite
|
Sign up to set email alerts
|

Body height differentiation by season of birth: Girls from Cracow, Poland

Abstract: Body height differentiation by season of birth: Girls from Cracow, PolandPublished studies world wide demonstrate that measures of human development and health status vary depending on the month of birth but these patterns are not always consistent and sometimes even conflict. Direct factors related to the birth season that may significantly differentiate morphological and functional traits and mechanisms causing these relations have not been found so far. On the basis of cross-sectional material, gathered in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Similarly, winter-born children have been reported to grow fastest in terms of height during childhood [10], [11]. On the other hand, another study reported that the growth in height of infants speeds up during the summer months, irrespective of month of birth [12].…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, winter-born children have been reported to grow fastest in terms of height during childhood [10], [11]. On the other hand, another study reported that the growth in height of infants speeds up during the summer months, irrespective of month of birth [12].…”
Section: Introductionmentioning
confidence: 97%
“…Associations have been widely reported between season of birth and a range of characteristics, including birth weight and length (Wohlfahrt et al, ; McGrath et al, , ; Torche and Corvalan, ; Krenz‐Niedbała et al, ) and body size in childhood (Kościński et al, ; Puch et al, ) and adulthood (Weber et al, ; Waldie et al, ). Season of birth associations with phenotype and health in developing countries are thought to reflect seasonal variation in diet, activity, and disease (Roberts et al, ; Adair and Pollitt, ; Moore et al, ; Rayco‐Solon et al, ; Chodick et al, ).…”
mentioning
confidence: 99%
“…Associations between birth month and body size persist into adulthood, suggesting that observed differences have their origin in prenatal or early postnatal life when growth trajectories are particularly sensitive to the environment (Smith et al, ; Lucas, ; Martorell et al, ; Schroeder et al, ; Mei et al, ; Dewey and Adu‐Afarwuah, ; Stein et al, ). While patterns may be expected to persist through childhood, studies investigating child height or body mass in relation to birth season provide mixed results in terms whether any patterns are observed, at what ages they are found, and when in the year the peaks and nadirs fall (Shephard et al, ; Henneberg and Louw, ; Waldie et al, ; Kościński et al, ; McGrath et al, ; Tanaka et al, ; Puch et al, ). This may in part relate to the fact that environmental factors like sunlight exposure or day length have separate effects on growth in childhood which may mask or modify patterns arising form birth season (Waldie et al, ).…”
mentioning
confidence: 99%
“…Comparing the age at menarche for subjects born in the summer months and in other months, the differences are statistically significant in both cohorts. Other studies carried out in Poland show that children born in the summer are characterized by inferior biological growth parameters in the early stages of their lives, as in linear enamel thickness ( _ Za˛dzi nska et al, 2013), body height (KrenzNiedbała et al, 2011;Puch et al, 2008), and body mass (Ko sci nski et al, 2009). In contrast, a study conducted by Siniarska and Kozieł (2010) showed that the birth length of boys is greatest in October and lowest in March and that in the first semiannual period the neonates are shorter than in the second (Siniarska and Kozieł, 2010).…”
Section: Discussionmentioning
confidence: 98%